Combination of heat treatment and chitosan coating to improve postharvest quality of wolfberry (Lycium barbarum). (10th January 2015) - Ban, Zhaojun; Wei, Wenwen; Yang, Xiangzheng; Feng, Jianhua; Guan, Junfeng; Li, Li
Summary: The synergistic application of hot water dip at 42 °C for 30 min and 1% chitosan coating on differentiation in postharvest quality traits, microstructure as well as microbiological evolution of wolfberry fruits was investigated. Fresh wolfberry fruits were stored at 2 ± 0.5 °C and 90% relative humidity (RH) for 28 days. Results indicated the combination of prestorage heat treatment and chitosan coating maintained higher levels of ascorbic acid, total phenolic contents and antioxidant capacity as well as lower decay, compared with untreated wolfberry fruits. The possible mechanism was that the heat treatment almost sealed open stomata to limit the sites of pathogen penetration into fruits independently, followed by the biofilm formed by chitosan which controlled secondary infections as well as slowed changes in fruit respiration and metabolic activity in wolfberries. The synergistically treated fruit also exhibited a higher acceptability obtained by sensory analysis after cold storage. In this sense, the integrated application of heat treatment and chitosan coating could be regarded as an effective strategy to extend storage life and maintain the postharvest quality of wolfberry fruits. Abstract : The integrated application of heat treatment and chitosan coating could be regarded as an effective strategy to extend storage life and maintain the postharvest quality of wolfberry fruits. The heat treatment almost sealed open stomata to limit the sites of pathogen penetration into fruits which could provide the first protection, followed by the bio‐film formed by chitosan which controlled secondary infections as well as slowed changes in fruit respiration and metabolic activity.